2017
DOI: 10.1007/s00068-017-0842-2
|View full text |Cite
|
Sign up to set email alerts
|

Routine versus selective chest and abdominopelvic CT-scan in conscious blunt trauma patients: a randomized controlled study

Abstract: Routine chest and abdominopelvic CT-scan in conscious blunt trauma patients decreases the hospitalization time, but has no impact on patient outcome and probably might lead to overtreatment of occult injuries. The option of using a selective approach should be further evaluated to decrease radiation exposure and facility overuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…The difference is an estimated excess cancer rate of 0.065% or 6.5/10 000 patients for patients undergoing WBCT compared to selective imaging. Although this may seem a very small number, our data and accumulated research suggests that this additional risk is being carried for no outcome benefit …”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The difference is an estimated excess cancer rate of 0.065% or 6.5/10 000 patients for patients undergoing WBCT compared to selective imaging. Although this may seem a very small number, our data and accumulated research suggests that this additional risk is being carried for no outcome benefit …”
Section: Discussionmentioning
confidence: 77%
“…Recently, WBCT scans have gained popularity in trauma centres for investigation of patients suffering severe trauma on the rationale that they more quickly and accurately identify injuries and allow earlier intervention if required. Their impact on patient outcome, compared to selective CT scanning, is the subject of some controversy and the risk of adverse events is not negligible. Although the logic underlying this practice might be reasonable for unconscious or critically ill patients, it is more tenuous in conscious or haemodynamically stable patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conscious and hemodynamically stable blunt trauma patients (mean ISS 8), Moussavi et al [2] prospectively assessed the relevance of performing routine versus selective (i.e., according to clinical presentation) chest and abdominalpelvic CT scan for hospitalization time and outcome after blunt trauma. In this study, a two-to-threefold increase of CT scans after routine CT utilization was observed.…”
mentioning
confidence: 99%